Pain status and sedation level in Chinese children after cardiac surgery: an observational study. Issue 1 (17th September 2012) - Bai, Jinbing; Hsu, Lily
<x xml:space="preserve">Abstract</x> Aims and objectives. This study explored current pain status, sedation level and their trajectories in Chinese children after cardiac surgery. Background. Pain and sedation management are fundamental care practices in the critical care setting, yet they both are frequently under‐implemented for children after major surgery. Design. Repeated observational design. Methods. This study was conducted in a paediatric medical centre in Shanghai, China where 170 children who underwent cardiac surgery were recruited. Pain was measured with the face, legs, activity, cry, consolability scale and sedation levels with the COMFORT Behaviour Scale at 18 fixed time‐points for three consecutive postoperative days. Results. The study indicated that 95 children (55·9%) received continuous opioids for pain relief, and 61 children (35·9%) received no analgesics. Multiple sedatives were used for these children, including bolus phenobarbital for 117 children (68·8%), phenergan for 81 children (47·6%) and midazolam for three children (1·8%). The mean pain scores significantly decreased throughout the operation day (POD‐0) to the 2nd postoperative day (POD‐2) with the lowest score on POD‐2. Less than 5% of pain assessments were identified as moderate to severe across all 2815 observations. The sedation scores significantly increased through POD‐0 to POD‐2 with the highest score on POD‐2. The rate of over‐sedation was 50·3% with <1% under‐sedation occurring among all the observations. Results also suggested that the length of stay in the cardiac intensive care unit was a predictor of increased analgesic usage in the critical care setting (odds ratio: 1·72). Conclusions. Usage of analgesic and sedative agents in cardiac intensive care unit was variable and children experienced low pain scores but a high rate of over‐sedation, indicating that healthcare providers should address ways to improve postoperative pain and sedation management in this population. Relevance to clinical practice. The pain and sedation status for children after cardiac surgery changed across the postoperative days. Healthcare providers should be trained in the use of reliable tools to accurately monitor children's pain and sedation levels.